Avoidance Measures for Patients with Allergic Rhinitis: A Scoping Review - Miguel Tomé; Olga Lourenço (MDPI AG, 2023)
Environmental allergen control is recommended as an essential part of allergic rhinitis (AR) management guidelines. In this scoping review, our objective is to identify measures of allergen avoidance and to evaluate their effectiveness in the management of AR. We conducted systematic searches for randomized controlled trials and observational studies in PubMed, the Cochrane Central Register of Controlled Trials, and the Web of Science databases. We included all types of control measures based on allergen eviction or reduction in exposure. Overall, 18 studies satisfied our criteria and were thus included for further analysis. The majority of the studies (15 out of 18) reported decreases in overall AR symptom scores, improvements in quality of life, or reductions in medication usage. However, due to the low number of participants and the limitations in study designs, it is not possible to make a definitive recommendation on the use of these interventions in the management of AR. A multifaceted approach, including treatment, prevention, and eradication of allergens from the environment, may be necessary to effectively reduce symptoms.